INTEGRASI ILMU AGAMA DAN SAINS DALAM PEMIKIRAN MUHAMMAD ABDUH: RELEVANSINYA TERHADAP KURIKULUM PESANTREN MODERN DI INDONESIA - Adji, Dhimas Nur’afif (CV. Jendela Gagasan, 2025)
The integrative discourse between religious sciences and modern sciences in Islamic education has long been debated, particularly within traditional educational institutions such as pesantren. Muhammad Abduh, as a pioneer of Islamic reform in the 19th century, offered an educational paradigm that combines religious values with scientific rationality. His ideas were a response to the stagnation of Islamic thought caused by the dominance of dogmatic methods that marginalized reason and science. For Abduh, religion and science are not contradictory entities, but rather two main pillars in shaping individuals who are both faithful and intellectually sound. This article aims to examine Abduh’s thought on the integration of religious and scientific knowledge and its relevance to the curriculum of modern pesantren in Indonesia. This study adopts a qualitative approach through library research, using primary sources such as Abduh’s Risalat al-Tauhid and secondary sources discussing Islamic education reform and pesantren transformation. The analysis is conducted using descriptive-analytical methods, focusing on the conceptual relationship between Abduh’s ideas and the current integrated curriculum practices in pesantren. The findings reveal that Abduh’s views on knowledge integration are highly relevant in addressing contemporary educational challenges. He emphasized the importance of reason as a tool to understand both revelation and the natural world. Modern sciences—such as mathematics, natural sciences, logic, and philosophy—are regarded as essential components of Islamic education rather than threats to faith. Abduh rejected the dichotomy of knowledge that separates “worldly sciences” from “religious sciences,” asserting that both are necessary to form holistic human beings. He strongly criticized the traditional educational systems that focused solely on religious instruction and failed to cultivate critical and scientific thinking. Abduh’s educational thought is reflected in the curricula of modern pesantren in Indonesia, which have undergone significant transformations. Institutions like Gontor, Trensains Tebuireng, and Anwarul Huda exemplify the integration of religious subjects with general sciences such as physics, biology, and mathematics. Furthermore, the use of dialogical and analytical teaching methods mirrors Abduh’s spirit of rationalism. Modern pesantren now serve not only as spiritual centers but also as intellectual hubs that prepare students to compete in a globalized world. By connecting Abduh’s thought with the educational practices of modern pesantren, this article concludes that an integrative educational approach is essential in responding to the demands of the times. A curriculum that nurtures both spiritual depth and critical-scientific skills is the ideal model for progressive Islamic education. Therefore, the future development of pesantren curricula should further embrace the integrative educational principles proposed by Abduh to produce graduates who are not only pious individuals but also socially and scientifically productive.